"Quem canta reza duas vezes": uma análise de canções Marianas de Lindbergh Pires. - Batista, Percy Marques (2018)
With the renewal of devotion to Mary, from the 70s of the twentieth century, through the support of the popes Paul VI and John Paul II, there was an urgent need to write songs in praise of the mother of Jesus. In view of this panorama, the Catholic Church had to opportunize the appearance of religious songs, so that there was a more active participation of the faithful in the celebrations, as opposed to the sacred repertoire used in the pre-conciliar past. It is in this context that the first liturgical compositions of the Ir Pires, SJ appear, of which, those of Marian themes, will only appear from the 90s until the years 2010, during which time he lived and worked in Recife, in front of the learned choir called Madrigal Unicap. In this sense, in order to make analyzes of these specifically Marian songs, it was necessary to go a long way, beginning the researches from the beginnings of the primitive Christianity until pouring into the religious music of liturgical character, backed in the current conciliar rules of Vatican II. The work thus contributes to the Sciences of Religion, when it brings, in the field of his research, important information about music, especially about the genre religious music. In the field of History of Music, renowned authors such as Candé (2003), Grout / Palisca (2005) and Palen ([1958]) were used as theoretical references in the field of Music History; already in the field of "mariology", we worked with renowned indoctrinators like Larentin (1965), Boff (2006), Lacoste (2004), Murad (2012) and Bauer (2000). In the same way, Doctrina dos Afetos and functional harmony (musical), were used as methodological tools of the analysis of these songs.